Vascular Tissue Relationships of the Prostate in Mature Rats with Chronic Alcoholism (Eurasian Journal of Learning and Academic Teaching, 2023)
The article analyzes the results of a study on the histological relationship between glandular and non-glandular structures of the prostate gland of mature rats and its structural changes in chronic alcoholism. In animals with chronic alcoholism, an increase in the diameter of the acini, a decrease in the volume fraction of the glandular parenchyma in the structure of the organ, and foci of epithelial stratification and cell proliferation are observed. Chronic exposure to alcohol leads to a pronounced degree of lymphocytic infiltration with lymphoid nodular formation, to a pronounced form of connective tissue proliferation, in the interglandular stroma the number and diameter of vessels increase and their wall thickness decreases